2017
DOI: 10.1007/s00234-017-1939-3
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal “gliosis only” on MR imaging represents a distinct entity in epilepsy patients

Abstract: "Gliosis only" has different MRI hippocampal characteristics than HS: less volume loss, less increase of the T2-w signal intensity, preservation of internal architecture, and more contralateral affection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 38 publications
5
22
0
1
Order By: Relevance
“…Importantly, clusters indicating atrophy were not observed in the investigated cohort, which is in line with a previous study demonstrating hippocampal T 2 changes in temporal lobe epilepsy, even in patients showing no signs of atrophy 14 . Furthermore, it has been reported that hippocampal gliosis may occur without atrophy 32 . Since T 2 depends on the free water content in tissue, 12,13 cortical reconstruction characterized by tissue damage and replacement of cells in nervous tissue by water on a microstructural level could potentially be another mechanism leading to increased cortical T 2 values in epilepsy patients with FCD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, clusters indicating atrophy were not observed in the investigated cohort, which is in line with a previous study demonstrating hippocampal T 2 changes in temporal lobe epilepsy, even in patients showing no signs of atrophy 14 . Furthermore, it has been reported that hippocampal gliosis may occur without atrophy 32 . Since T 2 depends on the free water content in tissue, 12,13 cortical reconstruction characterized by tissue damage and replacement of cells in nervous tissue by water on a microstructural level could potentially be another mechanism leading to increased cortical T 2 values in epilepsy patients with FCD.…”
Section: Discussionsupporting
confidence: 91%
“…14 Furthermore, it has been reported that hippocampal gliosis may occur without atrophy. 32 Since T 2 depends on the free water content in tissue, 12,13 cortical reconstruction characterized by tissue damage and replacement of cells in nervous tissue by water on a microstructural level could potentially be another mechanism leading to increased cortical T 2 values in epilepsy patients with FCD.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it has been demonstrated that hippocampal cell proliferation, as well as neurogenesis, could be promoted by chronic clomipramine treatment [ 14 , 57 ], which may account for the changes in hippocampal volume [ 58 , 59 ]. On the other hand, clomipramine likely increased the rat’s hippocampal volume by promoting gliosis, which could have something to do with the increase of hippocampal volume under pathological conditions [ 60 , 61 ] since our previous work indicated that chronic clomipramine treatment increased GFAP level in the hippocampus of rats exposed to chronic unpredictable stress [ 48 ]. Furthermore, Peixoto-Santos et al found that the extracellular matrix also plays an important role in the maintenance of hippocampal volume except for cellular constituents [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Als erwartbares Resultat aufgrund des geringeren Zellverlustes war die interne Histoarchitektur der Hippocampusformation besser erhalten. Interessanterweise zeigte sich die Gegenseite stärker in die Pathologie einbezogen [37]. Vor dem Hintergrund der Rolle von Astroglia als Immunzellen kann dieser Befund auch auf eine mögliche pathogenetisch relevante Rolle der Astroglia für die Emergenz der Schläfenlappenepilepsie und Anfallsentstehung spielen [38].…”
Section: Epilepsieassoziierte Tumorenunclassified